Examining the Concept of Sexual Health of Adolescent Students from the Perspective of Experts with a Focus on Parent Education - Saeede Memari; Hossein Khanifar; Golnar Mehran; Hamidreza Yazdani; Somayeh Fereiduni (Kerman University of Medical Sciences, 2019)
Introduction: Adolescence is one of the most important periods of life and adolescent behavioral characteristics are of great importance. Adolescents tend to overcome limitations and experience new behaviors; however, issues related to sexual health must be addressed. The main concern of the present study was to define the sexual health of adolescent students from the perspectives of experts and how these views can be sustained and promoted through parental education. Method: This qualitative study was conducted using qualitative content analysis. Data were collected using semi-structured interviews with 18 experts who were selected through purposive sampling with the Maximum diversity. The participants were individuals specialized in education, health, and juvenile issues. Results: After analyzing the data in the three stages of encoding, 20 subcategories, 7 main categories, and one theme were extracted. The findings indicate that sexual health is shaped in an inefficient sociocultural structure and also show the weaknesses in programs on sexual health education for parents and adolescents, which are influenced by social, familial, and individual factors. Conclusion: Sexual health is not limited to specific periods and is important from the birth throughout life. It requires special attention during adolescence. Although this stage requires the joint efforts of family and relevant organs and institutions related to health and education, family is the first and most important provider of sexual health and it must be provided with proper education.